Gender, Psychiatric and Cognitive Status Related to Experiential Auras in Patients with Temporal Lobe Epilepsy - Benjumea Cuartas, Vanessa (2018)
Objective: To determine whether the experiential auras in patients with temporal lobe epilepsy (TLE) are related to gender, psychiatric comorbidity, material-specific memory impairment, lateralization by video-EEG and structural neuroimaging abnormalities.Material and methods: Retrospective review (1998-2015) of clinical charts and video-EEG of patients with TLE and experiential auras followed at the JM Ramos Mejía and El Cruce Hospitals Results: We included 35 patients, 51.4% were male, mean age 35 years, mean epilepsy duration 20.3 years. Laterality of the epileptogenic zone was right (57.1%) and left (37.1%) temporal. An epileptogenic lesion was detected in most of cases and hippocampal sclerosis was the most common finding. Seventy-four percent of patients underwent epilepsy surgery (Engel I-II: 65.4%). The most frequent neuropsychological finding was visual memory deficit, and most patients had executive dysfunction. Almost half patients had a psychiatric comorbidity. Déjà vu was the most frequent experiential aura (60%), followed by jamais vu (20%), strangeness (20%), depersonalization (14.3%), dreaminess (11.4%), autobiographical memory recall (8.6%) and time perception alteration (5.7%). Most patients (62.9%) had a single experiential aura (déjà vu 54.5%, jamais vu 18.2%, strangeness 13.6%, depersonalization 9.1%, prescience 4.5%) associated with non-experiential auras in the majority of cases (81%).Conclusion: Most of patients presented a single experiential aura, most frequently déjà vu, associated with non-experiential auras, mainly fear. A right temporal lobe seizure focus was the most frequent, including for patients with déjà vu. In relation to gender, déjà vu was more common in male patients. A high prevalence of psychiatric comorbidity was observed and despite of the reduced number of cases, the 3 patients with psychosis presented déjà vu. Most of patients presented visual memory deficit associated with executive dysfunction.